2007
DOI: 10.1248/cpb.55.1563
|View full text |Cite
|
Sign up to set email alerts
|

Development and Optimization of Intravenous Puerarin Emulsions Formation by a Novel Complex-Phase Inversion-Homogenization Technology

Abstract: Puerarin is naturally isoflavone C-glycoside which was isolated from Pueraria lobota. It is traditionally used to reduce febrile symptoms and decrease myocardial consumption of oxygen, and it also can increase coronary artery blood flow and improve microcirculation. [1][2][3] Due to poor oral bioavailability, the commercial product puerarin i.v. is widely used in clinical. It is used for treatment of coronary artery disease, ischemic heart disease, cerebrovascular disease, coronarism and cerebral angio spasm i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 15 publications
0
5
0
1
Order By: Relevance
“…19 Box-Behnken design has been comprehensively adopted to optimize the process of formulations. [20][21][22][23] Those studies demonstrated the apparent advantage of Box-Behnken design utilization in the formulaoptimization process.…”
Section: Introductionmentioning
confidence: 90%
“…19 Box-Behnken design has been comprehensively adopted to optimize the process of formulations. [20][21][22][23] Those studies demonstrated the apparent advantage of Box-Behnken design utilization in the formulaoptimization process.…”
Section: Introductionmentioning
confidence: 90%
“…The entrapment efficiency (EE %) was determined according to a previously described method [17] . Briefly, the emulsions with drugs were centrifuged at 23 000 rpm for 1 h (4°C) in a Hermle ultracentrifuge (Hermle, Germany) to separate the incorporated drug and the non‐incorporated drug.…”
Section: Methodsmentioning
confidence: 99%
“…The entrapment efficiency (EE %) was determined according to a previously described method. [17] Briefly, the emulsions with drugs were centrifuged at 23 000 rpm for 1 h (4°C) in a Hermle ultracentrifuge (Hermle, Germany) to separate the incorporated drug and the non-incorporated drug. The concentrations of HCPT in the emulsion (n1) and free drug in the aqueous (the non-incorporated drug) (n2) were assayed by HPLC after dilution with methanol.…”
Section: Entrapment Efficiency Of Hydroxycamptothecin Submicron Emulsmentioning
confidence: 99%
“…77 Entretanto, outras técnicas mais precisas têm sido descritas, como a centrifugação, que exige a validação do tempo (que pode ser teoricamente calculado) e da velocidade de centrifugação, de forma a garantir que somente os cristais livres precipitem, em totalidade, para serem posterioremente lavados, dissolvidos em solvente adequado e quantificados. 48,70,78 Alguns autores têm utilizado também a cromatografia em coluna Sephadex, visando a separação das frações contendo o fármaco livre e associado, para posterior quantificação por cromatografia de alta eficiência. 12,55 Existem ainda as técnicas que se baseiam na passagem do fár-maco livre através de membranas de tamanho de poro conhecido: a ultrafiltração/centrifugação, que é a mais utilizada, e a microdiálise.…”
Section: Taxa De Associação Do Fármacounclassified